The sound of thunder - Torres, J., 1969- (Torres, J., 1969- Bigfoot boy, 2014)
"Rufus, Penny and their squirrel friend, Sidney, are eager to recapture the magic totem they lost to the ravens in the previous book. But how? With Rufus no longer in possession of his powers, the trio seems destined to fail. Their luck turns, however, when they learn the local legend of Thunderbird. It seems the mighty bird had created the magic totem decades earlier to be used to ward off developers who wanted to destroy the precious Pacific Northwest forest. Developers who were much like the ones cutting down their trees today! Empowered with a newfound purpose to protect the woods, they finally know just what they have to do to save the day -- and the trees!"--Publisher.